2022
DOI: 10.15282/ijame.19.4.2022.05.0779
|View full text |Cite
|
Sign up to set email alerts
|

Throttling Effect on the Performance and Emissions of a Multi-Cylinder Gasoline Fuelled Spark Ignition Engine

Abstract: The throttle mechanism, a regulatory technique of engine output, is accompanied by a loss of some energy. The effect of intake air throttling on the performance and emissions of a multi-cylinder spark ignition gasoline engine was experimentally investigated. The engine was coupled to a hydraulic dynamometer equipped with a customized cooling system for both the engine and dynamometer. Experimental tests were performed for various engine speeds and air-fuel ratios at the WOT and POT conditions with optimized ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…Consequently, the concentrations of CO 2 and NO x species increased; while the concentrations of CO and HC species in the exhaust stream decreased. This trend of the emitted gases indices as the throttle opening widen well matches with formerly published data [29]. However, there are inconsistencies in the values of other published works [39,48], which might be mainly owing to the smaller size of their tested engines.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Consequently, the concentrations of CO 2 and NO x species increased; while the concentrations of CO and HC species in the exhaust stream decreased. This trend of the emitted gases indices as the throttle opening widen well matches with formerly published data [29]. However, there are inconsistencies in the values of other published works [39,48], which might be mainly owing to the smaller size of their tested engines.…”
Section: Resultssupporting
confidence: 90%
“…It can be revealed that there was an increment in entropy generation under the POT condition compared to the WOT condition for all the tested engine speeds, except 2500 and 3500 rpm, which exhibited different trends. Such deviation of the entropy generation trend might be due to the mechanical failure of the throttle controller due to vibration resonance [29]. This trend is seemed to be governed in somewhat by the noticed trend of the AFR (see tables 5 and 6).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations